The Role of UTAUT Constructs In The Adoption of QRIS for Cash Waqf: Evidence from Islamic Economic Communities - Muhamad Haqiqi Maramis; Widiyanti Ayu Nilasari; Ririn Tri Ratnasari; Herry Aslam Wahid (JESI (Jurnal Ekonomi Syariah Indonesia), 2026)
Introduction: This study examines determinants of behavioral intention and actual adoption of QRIS for cash waqf within MES using the UTAUT framework, addressing low digital waqf uptake and limited evidence in community-based Islamic contexts. Methodology: A quantitative PLS-SEM approach (SmartPLS 4.0) was applied to online survey data from 133 MES administrators and members who have used QRIS for cash waqf. Result: The results show that performance expectancy, effort expectancy, and social influence have a positive and significant effect on intention to use QRIS. In contrast, facilitating conditions and behavioral intention do not significantly influence actual user adoption. Conclusion: Perceived benefits, ease of use, and social encouragement are key drivers of intention, yet intention does not necessarily translate into real behavior, indicating an intention–behavior gap in QRIS-based cash waqf. To improve adoption, stakeholders should strengthen perceived usefulness through clear value propositions, simplify the donation flow and feedback, leverage community networks, and implement community-based education to support sustained digital waqf participation. Implications: Limited to purposive sampling in one MES community and a cross-sectional self-reported survey, which may reduce generalizability and introduce common method bias. Future studies should use broader samples, longitudinal designs, and transaction data to better capture the intention–behavior gap. Originality: This study provides evidence on QRIS-based cash waqf adoption in a community setting by testing intention and actual use with a UTAUT-based PLS-SEM model, highlighting the intention–behavior gap and practical ways to improve conversion.